Địa tầng Kainozoi tại các đồng bằng ven biển Nam Trung Bộ - Dỹ, Nguyễn Địch; Thuận, Đinh Văn; Tấn, Nguyễn Trọng; Hà, Vũ Văn; Lương, Lê Đức; Pha, Phan Đông (Vietnam Journal of Earth Sciences, 2012)
summaryCenozoic stratigraphy of the coastal plains inthe South Central VietnamBy reviewing present stratigraphical divisions in the South Central Vietnam, the authors have given some following proposals :The Song Ba formation is dated of Middle - Late Miocene age ; both Di Linh and Kon Tum formations of Late Miocene - Early Pliocene age; the Mavieck one of Late Miocene - undivided Pliocene age andPhan Thiet of Middle - Late Pleistocene age were formed in marine condition. The Nha Trang formation, dated of Early - MiddleHolocene age with alluvio-marine genesis, should not be used because this name was previously published for another Cretaceous formation.The second river-terrace sediments, Song Luy Basalt of Late Pleistocene age and the Song Luy Formation of Pliocene age should be continued to study in their relationship.The proposed Cenozoic stratigraphical scale for the South Central coastal Plains of Vietnam is compo-sed of 14 divisions, of which, 4 for Neogene and 14 for Quaternary.